Analysis of Protein-Protein Interaction Network Based on Transcriptome Profiling of Human Induced Pluripotent Stem Cells Identifies Candidate Genes (Journal of Pharmaceutical Negative Results, 2022)
Human induced pluripotent stem cells (hiPSCs) offer an exceptional opportunity for generating disease-specific models to study and explorethe underlying mechanisms. The present study aims to perform bioinformatics analysis to explore the potential hub genes, cluster as wellas functional pathways depended upon the differentiation of induced pluripotent stem cells. Differentially expressed genes (DEGs) betweeninduced pluripotent stem cells (hiPSCs) and their differentiated cells (cardiomyocytes, CMs) were identified by TAC software. Subsequently,the protein-protein interaction (PPI) network was built using the differentially expressed genes (DEGs) and NetworkAnalyst tool, which thenanalyzed by Cytoscape software. The results disclosed that 3654 DEGs (1699 [46.49%] upregulated and 1955 [53.50%] downregulated) areprimarily implicated in the CMs differentiated from hiPSCs. The component of the main constructed PPI network comprised of 975 nodes with2472 edges. Six hub genes were recognized (MCM3, MCM5, CDC6, EP300, RPS27A, CDKN1A) by overlap of the top fifty genes as statedby five calculation methods in CytoHubba. In addition, five significant modules were generated using MCODE application in Cytoscape. Theresult of GO analysis for the five modules A-E, respectively, disclosed that DNA replication origin binding, structural constituent of ribosome,RNA binding, actin binding, exodeoxyribonuclease activity, producing 5’-phosphomonoesters are the most significantly enriched in molecularfunction term; DNA replication initiation, translational elongation, ribosome biogenesis, muscle filament sliding, ERBB2 signaling pathway arethe most significantly enriched in biological process term; chromosome, telomeric region, large ribosomal subunit, nucleolus, striated musclethin filament, basal plasma membrane are the most enriched in cellular component term. The KEGG pathway analysis disclosed that the genesof five modules A-E, respectively, were enriched in Cell cycle, Ribosome, Ribosome biogenesis in eukaryotes, Cardiac muscle contraction,ErbB signaling pathway.In conclusion, the analysis of DEGs and hub genes analysis play significant role in hiPSCs differentiation into CMsand could improve our understanding their differentiation.